Autophagy-dependent ferroptosis as a potential treatment for glioblastoma - Xie, Yangchun; Hou, Tao; Liu, Jinyou; Zhang, Haixia; Liu, Xianling; Kang, Rui; Tang, Daolin (Frontiers in Oncology, 2023)
Glioblastoma (GBM) is the most common malignant primary brain tumor with a poor 5-year survival rate. Autophagy is a conserved intracellular degradation system that plays a dual role in GBM pathogenesis and therapy. On one hand, stress can lead to unlimited autophagy to promote GBM cell death. On the other hand, elevated autophagy promotes the survival of glioblastoma stem cells against chemotherapy and radiation therapy. Ferroptosis is a type of lipid peroxidation-mediated regulated necrosis that initially differs from autophagy and other types of cell death in terms of cell morphology, biochemical characteristics, and the gene regulators involved. However, recent studies have challenged this view and demonstrated that the occurrence of ferroptosis is dependent on autophagy, and that many regulators of ferroptosis are involved in the control of autophagy machinery. Functionally, autophagy-dependent ferroptosis plays a unique role in tumorigenesis and therapeutic sensitivity. This mini-review will focus on the mechanisms and principles of autophagy-dependent ferroptosis and its emerging implications in GBM.